Other, Stranger and Compassion: Moral Changes in Individuals; Interpretation from “Suwanna Sam Jataka” - Boonnoon, Channarong (Journal of Buddhist Studies Chulalongkorn University, 2025)
This research article presents an interpretation of the concept of mercy (metta) in Buddhism through two key aspects: (1) What constitutes moral emotions (mercy); and (2) How can we develop moral emotions (mercy) towards others? This involves cultivating mercy within social life, especially when encountering others and strangers, whose cultural backgrounds may be different from, and even conflicting with, ours. The article first examines components of mercy in Buddhist teachings and in the works of Martha Nussbaum (2001). It then considers the moral transformation in individuals as illustrated in the story of "Suvanna Sama Jataka," interpreted through modern Western and Chinese philosophical concepts. The study finds that mercy in individuals includes both emotional and rational dimensions. Analyzing the Suvanna Sama Jataka story through philosophical lenses reveals that mercy can effect moral change in individuals if they are morally inspired and capable of recognizing and understanding the value and significance of virtues as essential for a good life and society. The steps for developing mercy in individuals are as follows: (1) Recognizing and respecting the otherness of others; (2) Understanding the lives and sufferings of others by exchanging memories or experiences of happiness and suffering through a language of generosity; and (3) Deeply evaluating others' desires within the framework of fairness and flourishing in life. The researcher believes this process can be applied to foster coexistence in a multicultural society.